The law-enforcement system in the civil rights and freedoms protection system: the international comparative aspect - Устінова-Бойченко, Ганна Миколаївна; Устінова-Бойченко, Г. М.; Устинова-Бойченко, Анна Николаевна; Ustinova-Boichenko, Hanna M.; Лоскутов, Тимур Олександрович; Лоскутов, Т. О.; Лоскутов, Тимур Александрович; Loskutov, Tymur O.; Білянська, Наталія Володимирівна; Білянська, Н. В.; Билянская, Наталия Владимировна; Bilianska, Nataliia V.; et al. (San Gregorio de Portoviejo University, 2020)
The article focuses on the problem of place determination of law-enforcement agencies in the civil rights and freedoms protection system. The emphasis is given to the analysis of international legal instruments in this sphere, in particular: the Convention for the Protection of Human Rights and Fundamental Freedoms; the International Covenant on Civil and Political Rights; the International Covenant on Economic, Social and Cultural Rights; the EU Charter of Fundamental Rights. The article has proved that law enforcement agencies are mainly aimed at ensuring and protection of human and citizen civil rights and freedoms in all spheres of social relations. Their mission is to provide the rule of law and order as well as to effect the sovereign will of the state in the whole territory. At the same time, the law-enforcement bodies are proved to have authority to use legal measures aimed at the limitation of civil rights and freedoms, and it is reflected at the level of international legal instruments. Also, it has been proved that at the level of national legislation, national governments must secure independently volumes, completeness, and boarders of measures undertook by law-enforcement agencies to limit legally a number of civil rights. All such cases must be specified and written in laws in such a way as to avoid misunderstanding. The conclusion has been reached that limits, and measures applied by law enforcement authorities to restrict the civil rights, must be adaptive, flexible, and not so detailed in law but shown in protocols and standards of police work. Thus, it is important that efficiency and limits of the possible limitation of civil rights by law-enforcement agencies are carried out under the control and monitoring on the part of Civil Society Institutes. Such monitoring and control are aimed at securing permanent correction of law enforcement actions model in the sphere of civil rights and freedoms protection.

Стаття присвячена проблемі визначення місця правоохоронних органів у системі захисту цивільних прав і свобод. Акцент робиться на аналізі міжнародно-правових документів у цій сфері, зокрема: Конвенція про захист прав людини та основних свобод; Міжнародний пакт про громадянські та політичні права; Міжнародний пакт про економічні, соціальні та культурні права; Хартія ЄС про основні права. Стаття доводить, що правоохоронні органи в основному спрямовані на забезпечення та захист громадянських прав і свобод людини і громадянина в усіх сферах суспільних відносин. Їхня місія полягає у забезпеченні законності та правопорядку, а також у здійсненні суверенної волі держави на всій території. Водночас, правоохоронним органам надано повноваження застосовувати правові заходи, спрямовані на обмеження громадянських прав і свобод, і це відображається на рівні міжнародно-правових документів. Крім того, було доведено, що на рівні національного законодавства національні уряди повинні забезпечувати незалежні обсяги, повноту та межі заходів, вживаних правоохоронними органами для юридичного обмеження низки цивільних прав. Усі подібні випадки повинні бути зазначені та записані в законах таким чином, щоб уникнути непорозуміння. Зроблено висновок, що обмеження та заходи, що застосовуються правоохоронними органами для обмеження цивільних прав, повинні бути адаптивними, гнучкими та не настільки деталізованими в законодавстві, а відображатись у протоколах та стандартах роботи поліції. Таким чином, важливо, щоб ефективність та межі можливого обмеження цивільних прав правоохоронними органами здійснювались під контролем та моніторингом з боку інститутів громадянського суспільства. Такий моніторинг та контроль спрямований на забезпечення постійної корекції моделі правоохоронної діяльності у сфері захисту цивільних прав і свобод.

Статья посвящена проблеме определения места правоохранительных органов в системе защиты гражданских прав и свобод. Акцент делается на анализе международно-правовых документов в этой сфере, в частности: Конвенция о защите прав человека и основных свобод; Международный пакт о гражданских и политических правах; Международный пакт об экономических, социальных и культурных правах; Хартия ЕС об основных правах. Статья доказывает, что деятельность правоохранительных органов в основном направлена на обеспечение и защиту гражданских прав и свобод человека и гражданина во всех сферах общественных отношений. Их миссия заключается в обеспечении законности и правопорядка, а также в осуществлении суверенной воли государства на всей территории. В то же время, правоохранительным органам предоставлены полномочия применять правовые меры, направленные на ограничение гражданских прав и свобод, и это отображается на уровне международно-правовых документов. Кроме того, было доказано, что на уровне национального законодательства национальные правительства должны обеспечивать независимые объемы, полноту и пределы мер, применяемых правоохранительными органами для юридического ограничения ряда гражданских прав. Все подобные случаи должны быть указаны и записаны в законах таким образом, чтобы избежать недоразумения. Сделан вывод, что ограничения и меры, применяемые правоохранительными органами для ограничения гражданских прав, должны быть адаптивными, гибкими и не столь детализированными в законодательстве, а отображаться в протоколах и стандартах работы полиции. Таким образом, важно, чтобы эффективность и пределы возможного ограничения гражданских прав правоохранительными органами осуществлялись под контролем и мониторингом со стороны институтов гражданского общества. Такой мониторинг и контроль направлен на обеспечение постоянной коррекции модели правоохранительной деятельности в сфере защиты гражданских прав и свобод.
Loskutov T. O. The law-enforcement system in the civil rights and freedoms protection system: the international comparative aspect / T. O. Loskutov, N. V. Bilianska, H. M. Ustinova-Boichenko, V. M. Beschastnyy, I. V. Dubivka // San Gregorio Magazine. – Special edition. – № 42. – San Gregorio de Portoviejo University, 2020. – Р. 10-19.
Keywords: law-enforcement system; civil rights and freedoms protection; international legal instruments; сoercive measures; Civil Society Institutions; law-enforcement activities; правоохоронна система; захист цивільних прав і свобод; міжнародно-правові документи; примусові заходи; інститути громадянського суспільства; правоохоронна діяльність; правоохранительная система; защита прав и свобод граждан; международно-правовые документы; принудительные меры; институты гражданского общества; правоохранительная деятельность; Research Subject Categories::LAW/JURISPRUDENCE